2017
DOI: 10.5603/fm.a2017.0037
|View full text |Cite
|
Sign up to set email alerts
|

The possible protective effect of L-arginine against 5-fluorouracil-induced nephrotoxicity in male albino rats

Abstract: 5-fluorouracil (5-FU) is a potent antineoplastic agent used for the treatment of various malignancies. The L-arginine nitric oxide (NO) pathway involved in the pathogenesis of chemotherapy induced kidney damage. This work investigated the beneficial mechanism of L-arginine supplementation in 5-FU induced nephropathy. Eighty male Wistar rats were divided into four equal groups: control group; L-arginine group (378 mg/rat/day for 4 weeks); 5-FU group (189 mg/rat/week for 4 weeks) and L-arginine for 1 week before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
4
10
0
1
Order By: Relevance
“…In the present study, the administration of L-arginine protects the kidney function from Cd and Pb intoxication as indicated by significant restoration of serum urea, uric acid, and creatinine. This corroborates with the findings of Badawoud et al (2017) in which L-arginine has been reported to protect 5-fluorouracil-induced nephrotoxicity through its antioxidant capacity. Cd and Pb-induced kidney dysfunction was most likely attributed to oxidant/antioxidant imbalance in the kidney which manifested by a significant increase of the lipid peroxidation biomarker MDA and a significant decrease in the activities of the antioxidant enzymes (SOD, CAT) and GSH level.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the administration of L-arginine protects the kidney function from Cd and Pb intoxication as indicated by significant restoration of serum urea, uric acid, and creatinine. This corroborates with the findings of Badawoud et al (2017) in which L-arginine has been reported to protect 5-fluorouracil-induced nephrotoxicity through its antioxidant capacity. Cd and Pb-induced kidney dysfunction was most likely attributed to oxidant/antioxidant imbalance in the kidney which manifested by a significant increase of the lipid peroxidation biomarker MDA and a significant decrease in the activities of the antioxidant enzymes (SOD, CAT) and GSH level.…”
Section: Discussionsupporting
confidence: 92%
“…It also prevents renal toxicity of ethanol as manifested by morphological and histological studies in male rats [35] . Similarity, Badawoud1 et al, [36] reported that L-arginine at dose level 378 mg/rat/day for 4 weeks has effective ability to improve biochemical and histological changes in 5-5-fluorouracil nephrotoxicity, as glomerulus sclerosis, degeneration of convoluted tubules and interstitial fibrosis.…”
Section: Introductionsupporting
confidence: 60%
“…Drug-induced renal injury is one of common causes of acute kidney injury and is characterized by high patient morbidity and mortality [18][19][20]. In this context, 5-FU induced glomeruloscelerosis, degeneration of convoluted tubules, and interstitial fibrosis with ultimate renal dysfunction [21].…”
Section: Introductionmentioning
confidence: 99%